2023
DOI: 10.3390/biology12030439
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CNGCs in Glycine max and Screening of Related Resistance Genes after Fusarium solani Infection

Abstract: Cyclic nucleotide-gated channels (CNGCs), non-selective cation channels localised on the plasmalemma, are involved in growth, development, and regulatory mechanisms in plants during adverse stress. To date, CNGC gene families in multiple crops have been identified and analysed. However, there have been no systematic studies on the evolution and development of CNGC gene families in legumes. Therefore, in the present study, via transcriptome analysis, we identified 143 CNGC genes in legumes, and thereafter, clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…In this study, seven CMLs, two CNGCs, one CDPK, and three WRKYs were identified, which were involved in H. brassicae stress response and differentially expressed in resistant and susceptible materials (Figure 6A). CNGCs were a type of non-specific cation channel, which was an important way for plants to resist against the invasion of pathogens by regulating Ca 2+ influx [34]. Compared with the susceptible materials, we found the expression of CNGC9 and CNGC19 were significantly higher than that in the resistant materials at 12 hpi.…”
Section: Discussionmentioning
confidence: 72%
“…In this study, seven CMLs, two CNGCs, one CDPK, and three WRKYs were identified, which were involved in H. brassicae stress response and differentially expressed in resistant and susceptible materials (Figure 6A). CNGCs were a type of non-specific cation channel, which was an important way for plants to resist against the invasion of pathogens by regulating Ca 2+ influx [34]. Compared with the susceptible materials, we found the expression of CNGC9 and CNGC19 were significantly higher than that in the resistant materials at 12 hpi.…”
Section: Discussionmentioning
confidence: 72%